Jump ship to freedom - Collier, James Lincoln, 1928-; Collier, Christopher, 1930- (New York : Bantam Doubleday Dell Books for Young Readers, 1987)
In 1787, a fourteen-year-old slave, anxious to buy freedom for himself and his mother, escapes from his dishonest master and tries to find help in cashing the soldier's notes received by his father for fighting in the Revolution.
"A Yearling book."
Booklist
Elementary School Library Collection (Bro-Dart)
Junior High School Library Catalog (Wilson)
5.4
5-8
Keywords: African Americans -- Fiction; Historical fiction; Slavery -- Fiction